How mechanical deformations contribute to the effectiveness of negative‐pressure wound therapy. Issue 4 (29th April 2013) - Daigle, Patrick; Despatis, Marc‐Antoine; Grenier, Guillaume
Abstract Negative‐pressure wound therapy (NPWT) has significantly improved healing rates and patient comfort since its inception. However, a considerable number of questions have been raised regarding its mechanisms of action. Many health care workers and researchers have attempted to clarify the role of NPWT in wound healing. The purpose of this perspective article is to assemble some of the concepts that have been put forward in order to propose an integrated view of the mechanisms involved in NPWT. Particular emphasis will be placed on mechanically induced tissue deformations and their involvement in some of the key processes of wound healing, including nutrient and oxygen transport, blood vessel formation, and cellular proliferation and differentiation, mainly of myofibroblasts.